New Highly Sulfonated Polythioethers as Polyelectrolyte Membranes for Water Electrolysis - de Azpiazu Nadal, Ignasi; Branco, Bruno; Tovar, Günter E.M.; Kerres, Jochen; Janssen, René A.J.; Reynaud, Stéphanie; Atanasov, Vladimir (ACS Polymers Au, 2025)
Herein, the synthesis and characterization of highly sulfonated poly(arylene thioethers) for application as polymer electrolyte membranes in water electrolysis are reported. In a first step, poly(arylene thioethers) were obtained by using mild reaction conditions of a polycondensation reaction between 4,4′-thiobisbenzenethiol and decafluorobiphenyl. In a second step, the resulting poly(arylene thioethers) were sulfonated by a fluorothiol displacement click reaction of the fluorinated monomers by sodium 3-mercapto-1-propanesulfonate. Thus, highly sulfonated polymers were obtained, resulting in water-soluble ionomers. Stable polymer electrolyte membranes with enhanced thermal and chemical stability were attained by blending ionomers with a poly(benzimidazole) derivative (PBI-OO). The resulting proton-exchange membranes (PEMs) based on the new sulfonated ionomer PBI-OO blends showed about 40% higher proton conductivity than Nafion at 90 °C. The proton-conducting membranes with the highest conductivity and best film-forming properties were applied for water electrolysis. Combined with optimized water oxidation and reduction catalysts, the selected tetra-sulfonated polymer-based PEM reached 1.784 V at 1 A cm-2 in the electrolysis of pure water.
CRIS-Team Scopus Importer:2025-02-07
Keywords: catalyst optimization; fluorinated poly(arylene thioether); polycondensation; proton-exchange membranes; sulfonated ionomers; water electrolysis